2007
DOI: 10.1097/brs.0b013e318074d539
|View full text |Cite
|
Sign up to set email alerts
|

A Detailed Morphologic and Functional Magnetic Resonance Imaging Study of the Craniocervical Junction in Adolescent Idiopathic Scoliosis

Abstract: Peak CSF velocities through foramen magnum were not significantly different in AIS subjects despite the presence of low-lying cerebellar tonsils. This might be explained by the compensatory effect of larger foramen magnum in AIS subjects.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
38
1
2

Year Published

2008
2008
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 40 publications
(44 citation statements)
references
References 20 publications
(28 reference statements)
3
38
1
2
Order By: Relevance
“…Most interesting, a correlative relationship was also found between the tonsillar level and abnormal FA values in AIS. Our proposed explanation for the above changes was that there was an anatomic compression of the relatively low-set cerebellar tonsil 9 onto the craniocervical junction. This subclinical type of cord compression might affect the neural pathway above and below the maximal area of compression (ie, the lower part of the brain stem [the medulla oblongata] and the upper cervical cord region).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Most interesting, a correlative relationship was also found between the tonsillar level and abnormal FA values in AIS. Our proposed explanation for the above changes was that there was an anatomic compression of the relatively low-set cerebellar tonsil 9 onto the craniocervical junction. This subclinical type of cord compression might affect the neural pathway above and below the maximal area of compression (ie, the lower part of the brain stem [the medulla oblongata] and the upper cervical cord region).…”
Section: Discussionmentioning
confidence: 99%
“…3 Previous studies have reported changes in central nervous system structures in patients with AIS based on advanced medical imaging modalities. [4][5][6] Furthermore in a number of MR imaging studies, the observable changes in morphologic shape and position of the cord, 7 mismatch in lengthening between the cord and vertebral column, 8 and increased incidence of low-lying cerebellar tonsils 9 have led to the postulation of the presence of subclinical tethering of the spinal cord in AIS. 10 The proposed disturbed spinal cord function in AIS was further supported by the clinical observation of abnormal somatosensory function, which has been widely reported in this group.…”
mentioning
confidence: 99%
“…Recent studies with MRI in idiopathic scoliosis supports this [16]. Neurosurgical articles on traction problems of the cord as in myelomeningocele do not refer to this intrinsic shortening depicted by Roth, but mainly on external tethering [17][18][19].…”
Section: Introductionmentioning
confidence: 71%
“…Chu [4][5][6] reported that the cross-sectional shape of the cord in AIS was not due to compression from the wall of the spinal canal by observation that the cross-sectional shape of the cord in severe AIS was fairly symmetrical using the MetaMorph Imaging System. Because compression force from one side should result in asymmetrical shape of the cord.…”
Section: Discussionmentioning
confidence: 99%